Percutaneous Cementoplasty to Treat Sternal Instability After Cardiac Surgery - Pittet, Thaïs; Cook, Stéphane; Khatchatourov, Gregory; Theumann, Nicolas (Frontiers in Cardiovascular Medicine, 2022)
Introduction Although rare, sternal pseudarthrosis is encountered after cardiac surgery and impacts the quality of life by triggering motion-dependent chest pain. We thought to describe its treatment by percutaneous cementoplasty and report the clinical follow-up of patients treated in our institution. Methods This case series is a retrospective study based on five patients who benefited from a sternal cementoplasty as a treatment for symptomatic pseudarthrosis after cardiac surgery. The progression of the symptoms was assessed during clinical follow-up using the Quebec back pain disability (QBPD) scale and Visual Analog Scale (VAS). Results None of the patients presented evidence of local complications or neurological disorders. The intra- et post-operative images show no major leak of the cement, no embolism and no damage to the internal mammary artery or the heart. All patients described an improved quality of life due to reduced pain in all-day clinical activities. The QBPD scores improved from 54.8 ± 29.3 to 30.0 ± 17.4 (p = 0.02) and the VAS from 7.0 ± 2.8 to 1.6 ± 1.6 (p = 0.01). Furthermore, three out of five patients could completely stop taking analgesics. Conclusion Sternal pseudarthrosis is a debilitating affliction that may complicate sternotomy after cardiac surgery. This series demonstrates that a more conservative approach such as cementoplasty can be successful in terms of reducing pain, and constitutes a promising technique in selected cases.